Perspektif Masyarakat Tentang Pemahaman Pmi di Hut Pmi Ke 77 Tahun Kota Medan - Eva Srirahmayani; Indah Widya Sipahutar; Tiara Arfiandini (Peneliti.net, 2023)
The Indonesian Red Cross (PMI) is a national association organization in Indonesia which is engaged in social humanity. The Indonesian Red Cross in Medan City has been established since the 1950s, since then PMI Medan City has spread kindness to the people of North Sumatra, especially Medan City through disaster management, blood donations, social assistance and coaching the younger generation and so on. The purpose of this research is to find out about the views and knowledge or perspectives of the Medan city community about PMI. This research is a type of qualitative research that uses descriptive qualitative methods with data collection techniques through observation, interviews, and documentation. The results of the study show that the breadth of understanding of the Medan city community about PMI and the various views or perspectives of the community towards the Medan city PMI